School Assistance Program Through Accreditation At SD Muhammadiyah 1 Bengkulu City - Adi Asmara; Risnanosanti Risnanosanti; Winda Ramadianti; Nyayu Masyita Ariani; Selvi Riwayati; Masri Masri; Rahmat Jumri (CV Media Inti Teknologi, 2022)
The Community Service Program (PPM) which was carried out aims to assist SD Muhammadiyah 1 Bengkulu City in compiling an IASP 2020-based accreditation form. In 2022, reaccreditation will be carried out. Based on the results of interviews with school principals and teachers, the school accreditation preparation team did not fully understand the 2020 IASP, the deadline for preparation for accreditation in the near future, insufficient physical evidence, incomplete accreditation guidelines, schools did not have time to conduct self-evaluations and lack of coordination. and communication between individuals and teams. Based on this, it is necessary to carry out assistance activities in preparation for accreditation. The method used is discussion and question and answer. The subject of this community service is the team that composes the accreditation form for SD Muhammadiyah 1 Bengkulu City. This activity has been carried out for 4 meetings, which include the socialization of IASP 2020, filling out accreditation forms, presenting the results of filling out forms, and evaluating forms. During this service activity, all teams have carried out the form preparation activities well. The result of this service activity is that SD Muhammadiyah 1 Bengkulu City has completed all components of the accreditation form and met the internal quality standard values.